Pendekatan Monodisipliner: Sosok Tokoh Dalam Pemahaman Novel Sastra Indonesia - Rokyanto Rokhyanto; Umi Salamah; Nurwakhid Nurwakhid (linguistic, literature, and teaching, 2021)
This Indonesian Literary Novel contains various kinds of incidents, such as events of real people living in the world, both mere fiction and reality. Every good literary work always carries ethical and moral messages, so that good literature always voices ethical, moral, and full of mandates. The problems in this paper are: what are the figures in Indonesian literary novels ?; what are the problems that exist in the character figures in Indonesian literary novels ?; (3) what are the details of the two problems in the Indonesian literary novel? The purpose of this paper is: want to study in detail, want to examine in detail the figure of a character in Indonesian literary novels and want to know in detail the problems that exist in the figure of the character and want to know a detailed description according to the two problems in Indonesian literary novels. This paper uses a qualitative approach, which data is in the form of words, phrases, sentences, in the dialogue of characters in Indonesian literary novels. Data collection techniques in this paper are: text analysis in the form of exposure to language in the novel. The results of this paper produce a character who cares for the poor, a Kiai who is always patient and does not have a sad face. The figure of an irresponsible mother, a husband and wife who divorced because of angry lust, a child who lacks gratitude, and a mother who is not honest.